THE EFFECT OF ENVIRONMENTAL SOCIAL GOVERNANCE ON FINANCIAL PERFORMANCE WITH THE COST OF CAPITAL AS AN INTERVENING VARIABLE - Widyo Nugroho, Bernadus Erwin Bagastian; Mulyasari, Windu (Management Science Research Journal, 2025)
This study aims to determine the effect of ESG on financial performance with the cost of capital as anintervening variable. The intervening variable in this study is the cost of capital as measured by theweighted average cost of capital (WACC) based on the company's annual report. The independentvariable in this study is Environmental Social Government (ESG) as measured using Thomson ReutersEikon. The dependent variable in this study is financial performance as measured by Return Of Asset(ROA). The population of this study in manufacturing and real estate sector companies listed on theIndonesia Stock Exchange (IDX) for the2019-2022 period. The sampling technique used in this methodis purposive sampling with a total sample of 156 data. The data analysis method in this studyuses multiple regression analysis with STATA 17 and path analysis with the help of an online sobelcalculator. The results of this study indicate that ESG disclosure has a positive effect on financialperformance, environmental disclosure has no significant positive effect on financial performance,social disclosure has no significant positive effect on financial performance, andgovernance disclosurehas no significant positive effect on financial performance.In addition, the cost of capital is unable to actas a mediator in the effect of ESG on financial performance.